Anti-inflammatory and antinociceptive effects of phonophoresis in animal models: a randomized experimental study - L.C.P. Cardoso; N.B. Pinto; M.E.P. Nobre; M.R. Silva; G.M. Pires; M.J.P. Lopes; G.S.B. Viana; L.M.R. Rodrigues (Brazilian Journal of Medical and Biological Research, 2019)
The aim of this study was to evaluate the therapeutic effects of ultrasound (US)-mediated phonophoresis alone or in association with diclofenac diethylammonium (DCF) administered topically in animal models of inflammation. A pre-clinical, prospective, and randomized experimental study of quantitative and qualitative nature was carried out. Phonophoresis was performed using a therapeutic ultrasound apparatus in two distinct models of acute inflammation. Edema was induced by an intraplantar injection of carrageenan and measured by plethysmography. The Hargreaves test was used to evaluate the antinociceptive activity and investigate the action of phonophoresis on tumor necrosis factor (TNF)-α production. A histological analysis with hematoxylin-eosin was used to evaluate tissue repair, and the expression of COX-2 was determined by immunohistochemical analysis. At the peak of inflammatory activity (3 h), treatment with US, US+DCF, and DCF significantly reduced edema formation compared to the control group. Treatment with US+DCF was more effective than treatment with US alone at both analyzed times. In the analysis of the antinociceptive activity, the treatments significantly increased the latency time in response to the thermal stimulus. Histopathological analysis revealed a reduction of the inflammatory infiltrates and immunohistochemistry demonstrated that the association was effective in reducing COX-2 expression compared to the control group. The association of DCF with US produced anti-inflammatory and antinociceptive effects in rat models of inflammation, which may be associated with inhibition of COX-2 and TNF-α production.